App Advisory in Research Library Websites: A Preliminary Study - Tracy, Daniel G. (Qualitative and Quantitative Methods in Libraries; Vol 2 No 3 (2013): September 2013 Issue, 2017)
This preliminary study examines the websites of U.S. research libraries in one consortium, the Committee on Institutional Cooperation (CIC), to determine the extent and variety of online app advisory services these libraries provide to patrons. App advisory, for the purposes of this study, refers to any suggestions of downloadable mobile applications (whether for phones, tablets, or other devices) for use by patrons. This still emerging phenomenon needs systematic study. I explore how these institutions provide app advisory content on their websites, and the kinds of apps included in their recommendations. The paper will also explore the methodological problems in discovering this content through the many layers of library websites, and areas of interest for further study.